Inflammatory bowel disease is associated with increased mucosal levels of bactericidal/permeability-increasing protein - Monajemi, H; Meenan, J; Lamping, R; Obradov, D O; Radema, S A; Trown, P W; Tytgat, G N; Van Deventer, S J (Gastroenterology (New York, N.Y. 1943), 1996)
Clinical sepsis seldom accompanies inflammatory bowel disease. The aim of this study was to measure colonic mucosal levels of the neutrophil product bactericidal/permeability-increasing protein (BPI), which kills gram-negative bacteria in addition to inactivating endotoxin. Enzyme-linked immunosorbent assay and immunohistochemistry for BPI were performed on homogenates and tissue secretions of biopsy specimens from patients with ulcerative colitis (n=11) and Crohn's disease (n=5) and from normal controls (n=5). Mucosal neutrophil content (144 +/- 23 vs. 35 +/- 9 neutrophils/mg protein; P<0.007) and BPI content (2.07 +/- 0.75 vs. 0.12 +/- 0.02 ng/mg protein; P<0.002) were greater in the colitis groups and correlated closely (r=0.68; P<0.001). This relationship held for both ulcerative colitis (P<0.002) and Crohn's disease (P<0.01) with a trend towards greater levels in Crohn's disease. There was a trend towards higher BPI levels with an increasing endoscopic inflammation score (grade I, 1.32 +/- 0.6 ng/mg protein; grade II, 2.82 +/- 1.4 ng/mg protein). Immunohistochemistry and the biopsy culture showed BPI to be both intracellular and extracellular, to be present in the crypt lumen, and to be released into incubating medium. Mucosal levels of BPI are increased in colitis. Such localization may ameliorate mucosal responses to gram-negative bacteria and their products.